2011
DOI: 10.1002/dc.21857
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial fine needle aspiration biopsy and rapid on‐site evaluation in the setting of superior vena cava syndrome

Abstract: There is a paucity of prospective data on flexible bronchoscopy with rapid on-site evaluation (ROSE) in the setting of superior vena cava (SVC) syndrome. The aims of this prospective study were to assess the diagnostic yield and safety of these investigations and specifically to evaluate the role of ROSE in limiting the need for tissue biopsies. Over a 5-year period 48 patients (57.4 ± 9.7 years) with SVC syndrome secondary to intrathoracic tumors underwent flexible bronchoscopy with TBNA and ROSE. Endobronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…studies. [27][28][29] The impacts of using ROSE were most noticeable in the improvement of sample adequacy when performed by pathologists and at centres where initial sample adequacy rates without ROSE were low. [30] ROSE was used in the current study and has been shown to increase the diagnostic yield in transthoracic FNAs of lung cancer as well as decreasing the procedure time.…”
Section: Discussionmentioning
confidence: 99%
“…studies. [27][28][29] The impacts of using ROSE were most noticeable in the improvement of sample adequacy when performed by pathologists and at centres where initial sample adequacy rates without ROSE were low. [30] ROSE was used in the current study and has been shown to increase the diagnostic yield in transthoracic FNAs of lung cancer as well as decreasing the procedure time.…”
Section: Discussionmentioning
confidence: 99%
“…However, no specific risk factors for bleeding in LTX recipients could be found [24]. FB and tissue sampling in patients presenting a superior vena cava syndrome has been reported to be safe [25]. Pulmonary hypertension (PH) could, at least theoretically, lead to excessive bleeding following TBLB, and current recommendations [5] suggest that TBLB should be performed with caution in patients with elevated pulmonary arterial pressure (PAP) [5].…”
Section: Risk Factorsmentioning
confidence: 99%